The effect of achievement motivation and expectation toward studentsâ learning achievement on Islamic education - Hidayati, Nurul (Institut Agama Islam Negeri (IAIN) Salatiga, 2017)
This research aims at figuring out the effect of studentsâ achivement motivation and expectation towards studentsâ learning achivementa t PAI subject at VII class in junior high school level in 2014. There were three schools involved in the research:Â SMP N 1 Salatiga, Salatiga SMP N 6, and SMP Muhammadiyah Salatiga. This is quantitative research with purposive sampling technique. The data collecting technique were questionnaires, test and documents. Questionnaires were to see the relation between studentsâ achievement motivation and expectation while test was used to gain data for learning achievement on PAI. The instruments for questionnaire were tested using validity and reliability test, normality test, autocorrelation test, F test, and coefficient determinant test. The data analysis used regression techniques. The findings of the research show that independent variables of achievement motivation (X1) and expectations (X2) influence the dependent variable of learning achievement (Y) by Yâ = 48.866 + 0.04 X1Â + 0.258 X2 . This implies that 1 value of achievement motivation and 1 value of exectation will result on 49.164 learning achievement in PAI subject.